Application of the Online Method with the Whatsapp Application to Increase Student Learning Motivation through Providing Classical Guidance Information Services in Class VII-1 Even Semester UPT SPF SMP Negeri 2 Sunggal Academic Year 2021/2022) - Siti Nurbaya (Journal of Educational Analytics, 2022)
This study aims to find out how to increase student motivation in Class VII-1 at UPT SPF SMP Negeri 2 Sunggal. This study uses a quantitative approach using the online method with the Whatsapp application. The subjects in this study were students of class VII-1 at UPT SPF SMP Negeri 2 Sunggal for the 2021/2022 academic year, with a total of 32 students consisting of 14 boys and 18 girls. The data collection technique was carried out using individual absorption percentage techniques and classical completeness, as well as by observing teachers about the implementation of service purchases through the use of online methods with the Whatsapp application. The results of this study are that the application of the online method with the Whatsapp application in class VII-1 can increase learning motivation in providing Guidance and Counseling material services. This can be seen from the results of student learning outcomes obtained from cycle I and cycle II, namely: 04% and 23%.